MEDIASI KETERLIBATAN KARYAWAN TERHADAP HUBUNGAN MANAJEMEN BAKAT DENGAN KINERJA PEGAWAI - Atika Anggi Hafsara; Mukhsin, Moh. (Jurnal Bisnis dan Kewirausahaan, 2024)
This research aims to investigate and analyze the influence of management talent on employee performance, by considering the role of employee involvement as a mediator. The methodological approach used is quantitative descriptive, with Bank BTN Syariah Serang as the research object and involving 100 respondents as the research sample. Survey data was obtained using a 1-1 interval scale and then analyzed using Smart PLS version 4.0 software. The findings of this research imply that: 1) talent management does not have a positive impact on employee performance; 2) talent management has a positive and significant impact on employee engagement; 3) employee involvement has a positive and significant impact on employee performance; 4) talent management has a positive impact on employee performance through the mediation of employee involvement